(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
This article explores the ecological and economic importance of beekeeping in the central region of Uzbekistan, while identifying the major environmental and biological stressors affecting honeybee colonies. The study highlights the negative impact of industrial emissions, chemical pesticides, heavy metals, and fungal or viral infections on bee health and colony survival. In the central agro-industrial zones, the intensified environmental burden has led to increased prevalence of diseases such as ascosphaerosis, aspergillosis, and varroatosis among honeybee populations